LIMITING WATER RESOURCES FOR AGRICULTURAL USES IN RANIA DISTRICT, SULAIMANI GOVERNORATE - SALEM, BARHAM M.; O. ESMAIL, AKRAM; T. RASHID, ALWAND (Journal of Duhok University, 2020)
This study was conducted during 19th August, 2018 to 12th February, 2019 in Rania district, Sulaimani governorate to classify the water of 24 springs, 25wells and 3 rivers for agricultural purpose. The results indicated that all the studied water had good or excellent class for irrigation depending on global systems of irrigation. On the other hand, depending on USDA classification (1954) the water of (44, 5, 2 and 1) locations had (C2S1, C3S1, C4S1 and C4S2) classes for irrigation purpose respectively. While the waters of 49 and 3 locations had excellent and very satisfactory class for livestock and poultry uses respectively. Depending on dissolved oxygen (DO mg l-1) value most of the studied water were suitable for fish culture, except the water of two locations were not suitable for all fish species due to low values of dissolved oxygen in these two locations which were 5.20 and 6.30 mg oxygen per ml water